Measuring inflation during the Pandemic with the benefit of hindsight - Aftab Chowdhury; Huw Dixon (Cardiff University, Cardiff Business School, 2023)
This study has adopted the actual household expenditure data from the national accountstoconstruct a true inflation rate (using the Fisher index) and found that the official inflationrateinthe 33 OECD countries was an overestimate of true inflation for 22 and underestimate in11countries in the first wave of the COVID-19 pandemic. The result obtained for the countrieswhere true inflation was higher than the official rate in this study matches the results obtainedbyCavallo (2020) and Reinsdorf (2020). However, a significant difference has been detectedfor thecountries where the official inflation exceeds the true measure in this study. The core reasonbehind the discrepancies is in the use of appropriate expenditure weights. This suggests cautionin using credit-card based expenditure data when spending behaviour has changed dramatically.
Keywords: C43; E01; E31; I10; 330; Coronavirus (COVID-19); Pandemic; Inflation measurement; Household Final Consumption Expenditure (HHFCE); Consumer Price Index (CPI)